2019
DOI: 10.3390/pathogens8010039
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial sialoglycosidases in Virulence and Pathogenesis

Abstract: Human oral microbiome and dysbiotic infections have been recently evidently identified. One of the major reasons for such dysbiosis is impairment of the immune system. Periodontitis is a chronic inflammatory disease affecting the tissues that surround and support the teeth. In the United States., approximately 65 million people are affected by this condition. Its occurrence is also associated with many important systemic diseases such as cardiovascular disease, rheumatoid arthritis, and Alzheimer’s disease. Am… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…Mass spectrometric analysis of extracellular products (ECP) from A. hydrophila that conferred 100% protection to catfish vaccinated with ECP when challenged with the pathogen two weeks post-vaccination showed several putative proteins that may serve as important immunogens, including chitinase, chitodextrinase, outer membrane protein 85, putative metalloprotease, extracellular lipase, hemolysin, and elastase [ 115 ]. Other enzymes like collagenase, lytic polysaccharide monooxygenase, sphingomyelin phosphodiesterase, methyltransferase, triacylglycerol lipase, exo-alpha-sialidase, deoxyribonuclease I, nucleotidyltransferase, class C beta-lactamase and SGNH/GDSL hydrolase family protein identified in this study as potential vaccine candidates have been implicated in the virulence of bacterial pathogen [ 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 ], and could be considered for a design of an effective polyvalent vaccine for finfish.…”
Section: Discussionmentioning
confidence: 99%
“…Mass spectrometric analysis of extracellular products (ECP) from A. hydrophila that conferred 100% protection to catfish vaccinated with ECP when challenged with the pathogen two weeks post-vaccination showed several putative proteins that may serve as important immunogens, including chitinase, chitodextrinase, outer membrane protein 85, putative metalloprotease, extracellular lipase, hemolysin, and elastase [ 115 ]. Other enzymes like collagenase, lytic polysaccharide monooxygenase, sphingomyelin phosphodiesterase, methyltransferase, triacylglycerol lipase, exo-alpha-sialidase, deoxyribonuclease I, nucleotidyltransferase, class C beta-lactamase and SGNH/GDSL hydrolase family protein identified in this study as potential vaccine candidates have been implicated in the virulence of bacterial pathogen [ 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 ], and could be considered for a design of an effective polyvalent vaccine for finfish.…”
Section: Discussionmentioning
confidence: 99%
“…Although sialidases have no known role in GBS pathogenesis ( Yamaguchi et al, 2016 ), these proteins were shown to be immunomodulatory in other bacterial species ( Aruni et al, 2011 ; Sudhakara et al, 2019 ) while simultaneously promoting biofilm production and metabolism of host sugars ( Hardy et al, 2017 ; Zaramela et al, 2019 ). The presence and abundance of sialidase was variable: the ST-1 and ST-17 MVs all contained sialidase, but the ST-12 MVs lacked it.…”
Section: Discussionmentioning
confidence: 99%
“…Neuraminidases (sialidases) are well-known modifying enzymes that can cleave sialic acid from glycans. Many types of bacteria produce neuraminidase with various specificities ( 11 ). Streptococcus pneumoniae , a common cause of sepsis, can produce neuraminidase to induce rapid desialylation and clearance of platelets during systemic S. pneumo-niae infection ( 12 ).…”
Section: Alterations In Host Glycosylation By Bacterial Glycosyltransferases and Glycosidasesmentioning
confidence: 99%